Unusual Spinal Dysraphic Lesions - Jose Roberto Tude Melo; Pollyana Pacheco; Luiz Eduardo Wanderley (Hindawi Limited, 2013)
Human tail and multiple spinal dysraphism are unusual congenital malformations. Human tail appeared as a prominent lesion from the lumbosacrococcygeal region, generally without connection between the tail and the neurospinal axis. Spinal dysraphisms are usually isolated, reaching 0.038% of incidence of multiple spinal dysraphisms in the same child. There were three cases described of unusual spinal dysraphic lesions: two cases of human tail and a case of a multiple thoracic myelomeningocele. The literature about diagnosis and treatment was reviewed. Microsurgical technique was performed to provide better exploration of the lesions, and resection could be done in those congenital malformations, without morbidity.